Crime Prevention Programs: Evidence for a Developing Country - Rodrigo Vergara.
This paper analyzes the impact of two anti-crime programs implemented in Chile in the late 1990s. The first (Quadrant Plan) is related to enhancing the quality of police work and the second one (Secure County Plan) to the involvement of the community in designing specific projects aimed at reducing the crime rate. It is found that only the Quadrant Plan has been successful in terms of reducing crime rates and has caused its impact through the effect of arrests in deterring crime. The Secure County program does not appear to have any impact on crime rates. It is also found that crime is associated with unemployment and that there is persistence in crime rates.Crime, anti-crime programs, GMM